Analisis Dampak Sosial dan Lingkungan dari Konflik Tenurial di Kawasan Hutan Kecamatan Popayato - Yusfriandi Dwi Ariesna; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Tenure conflicts in forest areas are long-standing structural issues in various regions of Indonesia, including Popayato Sub-district in Gorontalo Province. These conflicts arise from overlapping land claims between local communities, companies, and the state, directly affecting the socio-economic and ecological conditions of surrounding populations. This study aims to analyze the social and environmental impacts of tenure conflicts in Popayato's forest areas and assess the roles of stakeholders in seeking sustainable solutions. A qualitative case study approach was applied through in-depth interviews, field observations, and thematic analysis. Findings reveal that communities face restricted access to productive land and forest resources, disrupting livelihoods and local cultural sustainability. Ecologically, tenure disputes have triggered illegal land clearing and significant forest degradation. Local governments have made mediation efforts, yet face challenges in coordination and policy inconsistency. Civil society organizations play a crucial role in advocating community rights through participatory mapping and the promotion of legal recognition via social forestry schemes. This study recommends resolving tenure conflicts through collaborative approaches that uphold principles of social and ecological justice, including strengthening local institutions, participatory boundary mapping, and developing inclusive conservation-based business models. In doing so, sustainable forest management can be achieved by recognizing local rights and enhancing community participation in decision-making processes.